A pilot investigation into force production in tethered swimming as an individual monitoring tool - Wackwitz, T.; Pearson, S. (ISBS Proceedings Archive (Michigan), 2018)
Gaining an understanding of the physical capabilities and capacities that underpin the performance of a complex skill are important to help guide performance development at the elite level. The purpose of this study was to improve understanding of the force generating characteristics that relate to performance in elite swimmers. Three elite butterfly swimmers were tested over six weeks to examine the interactions between force-derived variables from 30 s of maximal tethered swimming and maximal 50m swimming performance, both performed using the butterfly stroke. Mean force, peak force and impulse per stroke all displayed very strong relationships with 50m swim time (r > -0.8) and distance per stroke (r > 0.8) in group analysis. Peak force and impulse per stroke were better than mean force at discriminating variations in performance for an individual.